Action Research: A Methodology for Organizational Change - Dale Pracht; Andrew Toelle; Brent Broaddus (EDIS, 2022)
Change is inevitable. When working within an organization, figuring out what needs to change can be a big issue. Having quality information available for use can make the decision process clearer and more effective. Action research is a methodology that can be used by people internal to an organization to identify what changes need to be made. This new 3-page publication of the UF/IFAS Florida 4-H Youth Development Program was written by Dale Pracht, Andrew Toelle, and Brent Broaddus.